Two-dimensional ferromagnetic material with high Curie temperature and preparation method thereof

By using liquid bromine as the transport medium and FeCl3·6H2O as the iron source when preparing FeGaCr ferromagnetic material, combined with plasma treatment and morphological regulation treatment, the problems of low Curie temperature and poor magnetic retention effect in the prior art are solved, and a two-dimensional ferromagnetic material with high Curie temperature and high magnetic properties are achieved.

CN119889857APending Publication Date: 2025-04-25BEIHANG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411948024.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

It is difficult to prepare two-dimensional ferromagnetic materials with high Curie temperatures in the prior art, and the yield and repeatability of the layered two-dimensional materials are low, resulting in a weakening of the magnetic retention effect of the material.

Method used

Liquid bromine is used as the transport medium, FeCl3·6H2O as the iron source, Ga powder and Cr powder as alloy elements. In the process of preparing FeGaCr ferromagnetic materials, the microstructure and magnetic properties of the material are optimized through plasma treatment and morphological regulation.

Benefits of technology

The Curie temperature and magnetic properties of two-dimensional ferromagnetic materials are improved, and the material maintains magnetic order and high saturation magnetization under room temperature conditions are achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119889857A_ABST
    Figure CN119889857A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of magnetic semiconductors, in particular to a two-dimensional ferromagnetic material with high Curie temperature and a preparation method thereof.The two-dimensional ferromagnetic material is prepared from Fe, Ga, Cr and a transmission medium according to the mass ratio of (2-5): 1: 1: (0.8-1.2), and the transmission medium is liquid bromine; the Fe is FeCl3. 6H2O, the Ga is Ga powder, and the Cr is Cr powder; the preparation method comprises the following steps: S1, preparation of a carbon nitride substrate; S2, preparation of layered crystals; and S3, post-treatment. The FeGaCr thin film material generates stress in the growth process by regularly changing the temperature gradient of the two temperature zones in the tube furnace in the thin film generation process, so that the dislocation formation of the two-dimensional ferromagnetic material is guided, the magnetism of the ferromagnetic layer is effectively enhanced, and meanwhile, the ferromagnetic layer also has relatively high room temperature stability, the saturation magnetization of the obtained two-dimensional material at room temperature reaches up to 1.227 emu / cm < 3 >, and the two-dimensional material still keeps magnetic orderliness when the saturation magnetization is greater than 310K.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of magnetic semiconductor technology, and in particular to a two-dimensional ferromagnetic material with a high Curie temperature and a preparation method thereof. Background Art

[0002] 2D Ferromagnetic Materials refer to two-dimensional materials with ferromagnetism, that is, materials that can still maintain long-range magnetic order within the thickness of a single unit cell layer. Compared with three-dimensional materials, the surface atoms of two-dimensional materials are almost completely exposed, the atomic utilization rate is high and easy to control, so they have attracted much attention from academia and industry; due to the special structure of this type of material, its magnetism can be controlled by external fields, such as magnetic field, electric field, stacking method, electrostatic doping, ion intercalation, strain and interface factors, and is usually composed of single or multi-layer graphene, molybdenum disulfide and other materials. With its unique physical properties and atomically thin thickness, two-dimensional ferromagnetic materials have broad application prospects in the fields of magnetic storage, magnetic sensing, magnetic recording, etc., and are the inevitable choice for the development of the next generation of small-sized and high-integration-density information storage devices.

[0003] Curie Temperature (Tc) refers to the temperature at which a magnetic material changes from ferromagnetism to paramagnetism. Above this temperature, the magnetization intensity of a magnetic material decreases with increasing temperature until it disappears. The existence of Curie temperature is a basic property of magnetic materials, which determines at what temperature the material can maintain its magnetism.

[0004] Two-dimensional ferromagnetic materials with high Curie temperatures can maintain their magnetism over a wider temperature range, which makes them more stable in high-temperature applications. For example, the magnetic permeability of some magnetic materials drops sharply after exceeding the Curie temperature. Therefore, in fields such as power equipment, materials with high Curie temperatures can provide more reliable performance. Two-dimensional ferromagnetic materials with high Curie temperatures can still maintain their magnetism at high temperatures, thereby ensuring the performance consistency of the material during processing.

[0005] At present, the main method for obtaining layered two-dimensional materials is to prepare crystals through chemical vapor transport (CVT) and chemical vapor deposition (CVD), and then obtain thin layers by mechanically exfoliating bulk materials. Mechanical exfoliation of bulk materials can directly exfoliate single or multi-layer two-dimensional materials from bulk materials, but its yield and repeatability are relatively low. Moreover, since these two methods involve many factors, the magnetic retention effect of the final product is easily weakened, making the Curie temperature of the two-dimensional ferromagnetic material finally prepared far below room temperature, which greatly limits the practical application of two-dimensional ferromagnetic semi-metallic materials. Summary of the invention

[0006] In order to solve the above problems, the present invention provides a two-dimensional ferromagnetic material with a high Curie temperature and a preparation method thereof.

[0007] The technical solution of the present invention is: a two-dimensional ferromagnetic material with a high Curie temperature, which is prepared from Fe, Ga, Cr and a transmission medium in a mass ratio of 2 to 5:1:1:0.8 to 1.2, wherein the transmission medium is liquid bromine; the Fe is FeCl3·6H2O, the Ga is Ga powder, and the Cr is Cr powder;

[0008] Description: Using liquid bromine as a transmission medium, FeCl3·6H2O as an iron source, Ga powder and Cr powder as alloying elements in the process of preparing FeGaCr ferromagnetic materials is helpful to improve the uniformity and production efficiency of the material, and can also adapt to high temperature environments, and work together to optimize the microstructure and magnetic properties of the material; at the same time, the present invention further improves the Curie temperature of the two-dimensional ferromagnetic material by utilizing the strong exchange interaction between Ga atoms and Fe atoms, thereby realizing the room temperature ferromagnetism of the two-dimensional material film.

[0009] The present invention also provides a method for preparing a two-dimensional ferromagnetic material with a high Curie temperature, comprising the following steps:

[0010] S1. Preparation of carbon nitride substrate

[0011] S1-1. At a temperature of 22 to 26° C., soak the carbon nitride sheet in 70 to 80% ethanol for 15 to 20 minutes, then rinse the treated carbon nitride sheet with clean water for 4 to 6 times, dry it naturally, and set it aside;

[0012] S1-2, placing the carbon nitride sheet in a plasma processor, evacuating the vacuum in the plasma processor to 0.02-0.04 mTorr, introducing argon gas, and then subjecting the carbon nitride sheet to plasma treatment at a temperature of 250-300 K; wherein the plasma power is 40-60 W, the plasma treatment time is 40-60 s, the gas flow rate is 60-70 sccm, and the gas pressure is 50-70 mTorr;

[0013] S1-3, performing morphology control treatment on the surface of the carbon nitride sheet after the plasma treatment so that the surface has gaps, thereby obtaining a carbon nitride substrate;

[0014] S2. Preparation of layered crystals

[0015] Fe, Ga, and Cr are sealed in a sealed quartz tube as precursors. The transmission medium is prepared and introduced into the quartz tube. Then, the tube is placed in a dual-temperature zone tube furnace and vacuumed to ≤10 -4Pa, and then adjust the temperature of the double temperature zone, where the temperature of one end after adjustment n times is recorded as T an The temperature at the other end is T bn , and a thin film is grown on the carbon nitride substrate prepared in step S1, and the film growth thickness is D n , when |T an -T bn When |≥150, the temperature adjustment is terminated and FeGaCr layered crystals are obtained;

[0016] Among them, T an , T bn Temperature change, D n The thickness change satisfies the following formula:

[0017] T an =T b(n-1) +25n×(-1) n+1 (1)

[0018] T bn =T a(n-1) -50n×(-1) n-1 (2)

[0019]

[0020] k is the coefficient, 0.3≤k≤0.5, T b0 is the initial temperature of one end, in °C, satisfying 900≤T b0 ≤1000; T a0 is the initial temperature of the other end, in °C, satisfying 850≤T a0 ≤950;D n is the film deposition thickness, in nm; n is the number of adjustments; t n is the interval between the nth temperature adjustment and the last temperature adjustment, in days, satisfying 2≤t n ≤4;

[0021] S3, post-processing

[0022] The FeGaCr layered crystals are chemically exfoliated and then the carbon nitride substrate is removed to obtain a two-dimensional ferromagnetic material with a high Curie temperature.

[0023] Description: The present invention changes the temperature gradient of the double temperature zones in the tube furnace during the film formation process by the above method, which can generate stress during the growth of FeGaCr thin film materials, thereby guiding the formation of dislocations and effectively enhancing the magnetism of the ferromagnetic layer. The saturation magnetization intensity of the obtained two-dimensional material at room temperature is as high as 1.227emu / cm 3, and still maintain magnetic order at room temperature; and the temperature gradient change under the above formula can achieve a high degree of optimization of the magnetization intensity and coercive force of the film, and the temperature gradient change within the scope of this application can effectively promote the arrangement of magnetic moments and the formation of magnetic domains in the film, thereby improving the magnetic properties of the film.

[0024] Furthermore, in step S1-3, the method of the morphology control processing is:

[0025] (1) Adding nano-silicon oxide particles, modified PU particles and a composite solvent to a mixing bottle in a mass ratio of 22 to 26:5 to 7:12 to 14, sealing the mixing bottle, and placing the mixing bottle in an oil bath at 55 to 58° C. and stirring for 10 to 11 hours to form a suspension; wherein the composite solvent in the mixing bottle is a mixture of N,N-dimethyl sulfoxide and N-methylpyrrolidone in a weight ratio of 1 to 1.5:1;

[0026] (2) taking 2 / 3 of the suspension and mixing them in a weight ratio of 8-10 suspension: 0.6-0.8 of pore-forming agent, stirring until molten, and then using a hot spray gun to evenly spray it on the surface of the carbon nitride sheet, standing for 15-20 minutes to form an interface layer with pores, and then continuing to raise the temperature of the oil bath to 85-88°C, and adding PEI particles accounting for 5-12wt.% of the mass fraction of the remaining suspension to the mixing bottle, stirring and dispersing for 5-7h to form a mixed solution, and again using a hot spray gun to evenly spray the mixed solution on the surface of the interface layer, standing for 15-20 minutes to obtain a buffer layer; wherein the thickness of the interface layer is 2-3μm, and the thickness of the buffer layer is 0.5-1μm;

[0027] (3) Finally, the carbon nitride sheet is heat treated at a temperature of 100 to 110° C. for 5 to 10 minutes to obtain a carbon nitride substrate.

[0028] Description: Introducing a buffer layer between the carbon nitride flakes and the FeGaCr ferromagnetic material can effectively utilize the performance of PEI particles to improve the interface performance and reduce the influence of the microporous structure on the material performance; PU particles can act as an interface modifier to promote the interaction between nano-silicon oxide, carbon nitride and ferromagnetic materials, improve the interface bonding ability, further improve the bonding effect of the interface layer, and also provide the flexibility and adhesion of the coating, so that the coating has better performance. By preparing the interface layer, the characteristics of nano-silicon oxide particles and modified PU particles can be utilized to effectively enhance the interface bonding ability between the two-dimensional ferromagnetic material and the carbon nitride substrate. The presence of micropores makes the carbon nitride flakes have a higher specific surface area, providing more deposition sites for the FeGaCr ferromagnetic material. At the same time, the FeGaCr ferromagnetic material is deposited on the carbon nitride flakes in a smaller size, which helps to increase its Curie temperature; the microporous structure also helps to improve the dispersibility of the FeGaCr ferromagnetic material on the carbon nitride flakes and prevent it from agglomerating. Good dispersion can ensure that the FeGaCr ferromagnetic material is evenly distributed on the carbon nitride flakes, thereby improving its overall magnetism; finally, heat treatment again can enable the interface layer to form a chemical bond with the carbon nitride surface, thereby enhancing the interface bonding.

[0029] Furthermore, in step (1), the preparation method of the modified PU particles is: at room temperature, the magnetic powder core material, the solvent and the dispersant are stirred and mixed at a rate of 100 to 300 r / min in a mass ratio of 8 to 12:4 to 6:2 to 3 to obtain a magnetic suspension, and then the temperature is adjusted to 80 to 100° C., the magnetic suspension and the PU particles are mixed in a ratio of 10 to 15 mL:4 to 8 g, and finally the temperature is raised to 120 to 140° C. for curing for 1 to 2 hours, washed with water and dried to obtain modified PU particles;

[0030] Description: Magnetic powder core materials have the characteristics of high magnetic permeability, low coercive force, high Curie temperature, low loss, etc. PU particles themselves are not magnetic. By mixing and modifying with magnetic powder core materials, PU particles can be given magnetism, further improving the magnetic attraction effect of two-dimensional ferromagnetic materials. By adjusting the mixing temperature of magnetic suspension and PU particles, it can be ensured that PU particles are evenly dispersed in the solvent to obtain a uniform magnetic distribution. Finally, heating and curing can effectively ensure the stable combination between PU particles and magnetic fillers. Water washing can remove excess solvent and unreacted components, and improve the performance of modified PU particles.

[0031] Furthermore, the solvent is dimethylformamide, n-butanol or n-hexane;

[0032] Description: The above solvents have good solubility for magnetic alloy powders and can effectively disperse the powders in the solvents, thereby facilitating the subsequent mixing and magnetization process with PU particles; they have good compatibility with PU particles and can promote uniform mixing between magnetic alloy powders and PU particles; they have low toxicity and environmental impact and are low in cost.

[0033] Further, the dispersant is polyacrylic acid or sodium dodecyl sulfate;

[0034] Description: Sodium dodecyl sulfate can reduce the interfacial tension between the magnetic powder core material and the PU particles, and promote the uniform dispersion of the magnetic powder core material in the PU particles. Polyacrylic acid can form a protective layer by adsorbing on the surface of the magnetic powder core material to prevent the magnetic powder core material from agglomerating, and at the same time improve the dispersion stability of the magnetic powder core material in the PU particles.

[0035] Furthermore, in step (2), the pore-forming agent comprises, by weight percentage, 25-30% polystyrene, 15-20% carbon black, 5-8% diatomaceous earth, and the remainder sodium chloride particles;

[0036] Description: Carbon black is a black powder composed of carbon, which can improve the magnetic permeability of ferromagnetic materials. Diatomaceous earth is a natural non-metallic mineral with good adsorption and filtration capabilities, and can be used to optimize the surface properties of ferromagnetic materials. Sodium chloride particle pore formers are soluble in water and can be easily removed from the coating to reduce environmental pollution. Coatings with fine pore structures can improve the magnetic exchange of two-dimensional ferromagnetic materials, thereby increasing their Curie temperature. The introduction of polystyrene can regulate the pore structure and pore size distribution of the material, thereby affecting the formation of magnetic domains and the magnetization process, and further improving the magnetic properties of two-dimensional ferromagnetic materials.

[0037] Further, in step S3, the chemical stripping method is: immersing the FeGaCr layered crystal in a mixed solvent of 800-1000 mL of dimethylformamide and acetone in an equal mass ratio, and then heating to 65-75° C. until the interface layer is completely dissolved, thereby achieving separation of the FeGaCr two-dimensional ferromagnetic material and the carbon nitride substrate;

[0038] Description: The interface layer on the surface of the carbon nitride substrate is dissolved by the immersion method, thereby realizing the separation of the two-dimensional ferromagnetic material. The mixed solvent prepared by dimethylformamide and acetone has a higher efficiency in dissolving the interface layer and has the corresponding solubility for nano-silicon oxide particles and modified PU particles. At the same time, it has little effect on the carbon nitride substrate and FeGaCr ferromagnetic material. Temperature control within the above range can ensure that the dissolution effect of the composite solvent is optimal.

[0039] Furthermore, after the temperature is raised, ultrasonic waves are simultaneously applied to perform oscillation treatment, and the parameters of the oscillation treatment are: ultrasonic frequency of 20 to 25 kHz, ultrasonic power of 80 to 100 W, and ultrasonic time of 20 to 30 min;

[0040] Note: The above setting can further enhance the dissolution effect of the composite solvent on the interface layer.

[0041] The beneficial effects of the present invention are:

[0042] (1) The present invention can generate stress in the process of growing FeGaCr thin film materials by regularly changing the temperature gradient of the double temperature zones inside the tube furnace during the thin film formation process, thereby guiding the formation of dislocations and effectively enhancing the magnetism of the ferromagnetic layer. The saturation magnetization intensity of the obtained two-dimensional material at room temperature is as high as 1.227emu / cm 3 , and still maintain magnetic order at room temperature; and the temperature gradient change under the above formula can achieve a high degree of optimization of the magnetization intensity and coercive force of the film. At the same time, the temperature gradient change within the scope of this application can effectively promote the arrangement of magnetic moments and the formation of magnetic domains in the film, thereby improving the magnetic properties of the film.

[0043] (2) The present invention can utilize the characteristics of nano-silicon oxide particles and modified PU particles to effectively enhance the interfacial bonding ability between the two-dimensional ferromagnetic material and the carbon nitride substrate by preparing an interface layer. The presence of micropores enables the carbon nitride sheet to have a higher specific surface area, providing more deposition sites for the FeGaCr ferromagnetic material. At the same time, the FeGaCr ferromagnetic material is deposited on the carbon nitride sheet in a smaller size, which helps to increase its Curie temperature. Then, by introducing a buffer layer between the carbon nitride sheet and the FeGaCr ferromagnetic material, the PEI particles can be effectively utilized to improve the interface performance while reducing the influence of the interface discontinuity caused by the microporous structure on the material performance.

[0044] (3) The present invention imparts magnetism to PU particles by modifying the mixture of PU particles and magnetic powder core materials, thereby further improving the magnetic attraction effect of the two-dimensional ferromagnetic material. By adjusting the mixing temperature of the magnetic suspension and the PU particles, it is possible to ensure that the PU particles are evenly dispersed in the solvent to obtain a uniform magnetic distribution. Finally, the temperature is raised and solidified to effectively ensure the stable bonding between the PU particles and the magnetic filler, thereby further improving the performance of the modified PU particles. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 It is a trend diagram of the (anti) ferromagnetic transition temperature of the two-dimensional ferromagnetic materials prepared in Examples 1 to 9 of the present invention and Comparative Examples 1 to 3;

[0046] Figure 2is a saturation magnetization intensity variation trend diagram of the two-dimensional ferromagnetic materials prepared in Examples 1 to 9 of the present invention and Comparative Examples 1 to 3;

[0047] Figure 3 It is a trend diagram of the (anti) ferromagnetic transition temperature of the two-dimensional ferromagnetic materials prepared in Example 1, Example 10 to Example 19 and Comparative Examples 4 to 5 of the present invention;

[0048] Figure 4 It is a saturation magnetization intensity variation trend diagram of the two-dimensional ferromagnetic materials prepared in Example 1, Example 10 to Example 19 and Comparative Examples 4 to 5 of the present invention;

[0049] Figure 5 It is a trend diagram of the (antiferromagnetic) transition temperature of the two-dimensional ferromagnetic materials prepared in Example 1, Example 20 to Example 21 and Comparative Examples 6 to 7 of the present invention;

[0050] Figure 6 It is a saturation magnetization intensity variation trend diagram of the two-dimensional ferromagnetic materials prepared in Example 1, Example 20 to Example 21 and Comparative Examples 6 to 7 of the present invention;

[0051] Figure 7 It is a trend diagram of the (antiferromagnetic transition temperature of the two-dimensional ferromagnetic materials prepared in Example 1 and Example 22 to Example 26 of the present invention;

[0052] Figure 8 This is a trend diagram of the saturation magnetization intensity change of the two-dimensional ferromagnetic materials prepared in Example 1 and Example 22 to Example 26 of the present invention. DETAILED DESCRIPTION

[0053] In order to further illustrate the method adopted by the present invention and the effect achieved, the technical solution of the present invention will be clearly and completely described in combination with experiments below.

[0054] Embodiment 1: A two-dimensional ferromagnetic material with a high Curie temperature is prepared by mixing Fe, Ga, Cr and a transmission medium in a mass ratio of 3:1:1:1, wherein the transmission medium is liquid bromine; Fe is FeCl3·6H2O, Ga is Ga powder, and the Cr is Cr powder;

[0055] This embodiment also provides a method for preparing a two-dimensional ferromagnetic material with a high Curie temperature, comprising the following steps:

[0056] S1. Preparation of carbon nitride substrate

[0057] S1-1. At a temperature of 24° C., the carbon nitride sheet was soaked in 75% ethanol for 17 minutes, and then the treated carbon nitride sheet was rinsed 5 times with clean water, dried naturally, and set aside;

[0058] S1-2, placing the carbon nitride sheet in a plasma processor, evacuating the vacuum in the plasma processor to 0.03 mTorr, introducing argon gas, and then performing plasma treatment on the carbon nitride sheet at a temperature of 275 K; wherein the plasma power is 50 W, the plasma treatment time is 50 s, the gas flow rate is 65 sccm, and the gas pressure is 60 mTorr;

[0059] S1-3, performing morphology control treatment on the surface of the carbon nitride sheet after the plasma treatment to obtain a carbon nitride substrate;

[0060] In step S1-3, the method of morphology control processing is:

[0061] (1) Adding nano-silicon oxide particles, modified PU particles and a composite solvent into a mixing bottle in a mass ratio of 24:6:13, then sealing the mixing bottle, and placing the mixing bottle in an oil bath at 57° C. and stirring for 10.5 hours to form a suspension; wherein the composite solvent in the mixing bottle is a mixture of N,N-dimethyl sulfoxide and N-methylpyrrolidone in a weight ratio of 5:4;

[0062] The preparation method of the modified PU particles is as follows: at room temperature, the magnetic powder core material, the solvent and the dispersant are stirred and mixed at a mass ratio of 4:2:4 at a rate of 200r / min to obtain a magnetic suspension, and then the temperature is adjusted to 90°C, the magnetic suspension and the PU particles are mixed in a ratio of 13mL:6g, and finally the temperature is raised to 130°C for curing for 1.5h, washed with water and dried to obtain modified PU particles; the solvent is dimethylformamide; the dispersant is sodium dodecyl sulfate; optionally, the magnetic powder core material is any one of an iron powder core, a permalloy powder core and a sendustine powder core; wherein the magnetic powder core material in this embodiment uses a commercially available iron powder core;

[0063] (2) taking 2 / 3 of the suspension and mixing them in a weight ratio of 9:0.7, stirring until molten, and then using a hot spray gun to evenly spray it on the surface of the carbon nitride sheet, letting it stand for 18 minutes to form an interfacial layer with pores, and then continuing to raise the temperature of the oil bath to 86°C, and adding PEI particles accounting for 9wt.% of the mass fraction of the remaining suspension to the mixing bottle, stirring and dispersing for 6 hours to form a mixed solution, and again using a hot spray gun to evenly spray the mixed solution on the surface of the interface layer, letting it stand for 18 minutes to obtain a buffer layer; wherein the thickness of the interface layer is 2.5μm, and the thickness of the buffer layer is 0.8μm; the pore-forming agent, in terms of mass percentage, includes 27% polystyrene, 18% carbon black, 7% diatomaceous earth and the remainder of sodium chloride particles;

[0064] (3) finally, the carbon nitride sheet is subjected to a heat treatment at 105° C. for 8 minutes to obtain a carbon nitride substrate;

[0065] S2. Preparation of layered crystals

[0066] Fe, Ga, and Cr were sealed in a sealed quartz tube as precursors. The transmission medium was prepared and passed into the quartz tube. Then, the tube was placed in a dual-temperature zone tube furnace and evacuated to 10 -4 Pa, and then adjust the temperature of the double temperature zone, where the temperature of one end after adjustment n times is recorded as T an The temperature at the other end is T bn , and a thin film is grown on the carbon nitride substrate prepared in step S1, and the film growth thickness is D n , when |T an -T bn When |≥150, the temperature adjustment is terminated and FeGaCr layered crystals are obtained;

[0067] Among them, T an , T bn Temperature change, D n The thickness change satisfies the following formula:

[0068] T an =T b(n-1) +25n×(-1) n+1 (1)

[0069] T bn =T a(n-1) -50n×(-1) n-1 (2)

[0070]

[0071] In this embodiment, k is 0.4, T b0 is the initial temperature of one end, which is 950℃; T a0 is the initial temperature of the other end, which is 900℃; D n is the thickness of the nth film deposition, in nm; n is the number of adjustments; each interval t n =Temperature adjustment every 3 days;

[0072] It is calculated that during the first temperature change: T a1 =950+25×1×(-1) 2 =975℃; T b1 =900-50×1×(-1) 0 =850℃, D1=0.4(975-850) / (5×3)=3.33nm;

[0073] During the second temperature change, T a2 =850+25×2×(-1) 3 =800℃; T b2 =975-50×2×(-1) 1 =875℃, D2=0.4(875-800) / (5×3)=2nm;

[0074] During the third temperature change, T a3 =875+25×3×(-1) 4 =950℃; T b2 =800-50×3×(-1) 2 =650℃, D3=0.4(950-650) / (5×3)=8nm;

[0075] At this time, 950-650>150, after completing the third temperature change, the gradient temperature change ends, and a FeGaCr layered crystal with a thickness of 13.33nm is obtained;

[0076] S3, post-processing

[0077] The FeGaCr layered crystals are chemically exfoliated and then the carbon nitride substrate is removed to obtain a two-dimensional ferromagnetic material with a high Curie temperature.

[0078] In step S3, the chemical stripping method is: immerse the FeGaCr layered crystals in 900 mL of a mixed solvent of dimethylformamide and acetone in equal mass ratios, and then heat to 70°C until the interface layer is completely dissolved, thereby achieving separation of the FeGaCr two-dimensional ferromagnetic material and the carbon nitride substrate.

[0079] Example 2: The difference from Example 1 is that, S1-2, the carbon nitride thin sheet is placed in a plasma processor, the vacuum in the plasma processor is evacuated to 0.02mTorr, argon gas is introduced, and then the carbon nitride thin sheet is plasma treated at a temperature of 250K; wherein the plasma power is 40W, the plasma treatment time is 60s, the gas flow rate is 60sccm, and the gas pressure is 70mTorr.

[0080] Example 3: The difference from Example 1 is that, S1-2, the carbon nitride thin sheet is placed in a plasma processor, the vacuum in the plasma processor is evacuated to 0.04 mTorr, argon gas is introduced, and then the carbon nitride thin sheet is plasma treated at a temperature of 300 K; wherein the plasma power is 60 W, the plasma treatment time is 40 s, the gas flow rate is 70 sccm, and the gas pressure is 50 mTorr.

[0081] Example 4: Different from Example 1, in the morphology control treatment method (1) of step S1-3, nano-silicon oxide particles, modified PU particles and composite solvent are added to a mixing bottle in a mass ratio of 22:5:12, and then the mixing bottle is sealed and placed in an oil bath at 55°C for 11 hours to form a suspension.

[0082] Example 5: Different from Example 1, in the method (1) of the morphology control treatment of step S1-3, nano-silicon oxide particles, modified PU particles and composite solvent are added to a mixing bottle in a mass ratio of 26:7:14, and then the mixing bottle is sealed and placed in an oil bath at 58°C for 10 hours to form a suspension.

[0083] Example 6: Different from Example 1, in the method (1) of the morphology control treatment in step S1-3, the composite solvent in the mixing bottle is a mixture of N,N-dimethyl sulfoxide and N-methylpyrrolidone in a weight ratio of 1:1.

[0084] Example 7: Different from Example 1, in the method (1) of the morphology control treatment in step S1-3, the composite solvent in the mixing bottle is a mixture of N,N-dimethyl sulfoxide and N-methylpyrrolidone in a weight ratio of 1.5:1.

[0085] Example 8: Different from Example 1, in the morphology control treatment method (1) of step S1-3, the preparation method of the modified PU particles is: at room temperature, the magnetic powder core material, solvent and dispersant are stirred and mixed at a mass ratio of 2:1:2 at a rate of 100 r / min to obtain a magnetic suspension, and then the temperature is adjusted to 80°C, the magnetic suspension and PU particles are mixed in a ratio of 5mL:2g, and finally the temperature is raised to 120°C for curing treatment for 2h, washed with water and dried to obtain modified PU particles.

[0086] Example 9: Different from Example 1, in the morphology control treatment method (1) of step S1-3, the preparation method of the modified PU particles is: at room temperature, the magnetic powder core material, solvent and dispersant are stirred and mixed at a mass ratio of 4:2:1 at a rate of 300 r / min to obtain a magnetic suspension, and then the temperature is adjusted to 100°C, and the magnetic suspension and PU particles are mixed in a ratio of 15mL:8g. Finally, the temperature is raised to 140°C for curing treatment for 1h, washed with water and dried to obtain modified PU particles.

[0087] Example 10: Different from Example 1, in the method (2) of the morphology control treatment of step S1-3, 2 / 3 of the suspension is taken and mixed according to a weight ratio of suspension: pore-forming agent of 8:0.6, stirred to a molten state, and then evenly sprayed on the surface of the carbon nitride sheet using a hot spray gun, and allowed to stand for 15 minutes to form an interface layer with pores.

[0088] Example 11: Different from Example 1, in the method (2) of the morphology control treatment of step S1-3, 2 / 3 of the suspension is taken and mixed according to a weight ratio of suspension: pore-forming agent of 10:0.8, stirred until molten, and then evenly sprayed on the surface of the carbon nitride sheet using a hot spray gun, and allowed to stand for 20 minutes to form an interface layer with pores.

[0089] Example 12: Different from Example 1, in the method (2) of morphology control treatment in step S1-3, the temperature of the oil bath is then raised to 85°C, and PEI particles accounting for 5 wt.% of the remaining suspension are added to the mixing bottle, stirred and dispersed for 5 hours to form a mixed solution, and the mixed solution is again evenly sprayed on the surface of the interface layer using a hot spray gun, and allowed to stand for 15 minutes to obtain a buffer layer.

[0090] Example 13: Different from Example 1, in the method (2) of morphology control treatment in step S1-3, the temperature of the oil bath is then raised to 88°C, and PEI particles accounting for 12 wt.% of the remaining suspension are added to the mixing bottle, stirred and dispersed for 7 hours to form a mixed solution, and the mixed solution is again evenly sprayed on the surface of the interface layer using a hot spray gun, and allowed to stand for 20 minutes to obtain a buffer layer.

[0091] Example 14: Different from Example 1, in the method (2) of morphology control treatment in step S1-3, the thickness of the interface layer is 2 μm, and the thickness of the buffer layer is 0.5 μm.

[0092] Example 15: Different from Example 1, in the method (2) of morphology control treatment in step S1-3, the thickness of the interface layer is 3 μm and the thickness of the buffer layer is 1 μm.

[0093] Example 16: Different from Example 1, in the method (2) of the morphology control treatment in step S1-3, the pore-forming agent includes, by mass percentage, 25% polystyrene, 15% carbon black, 5% diatomaceous earth and the remainder sodium chloride particles.

[0094] Example 17: Different from Example 1, in the method (2) of morphology control treatment in step S1-3, the pore-forming agent includes, by mass percentage, 30% polystyrene, 20% carbon black, 8% diatomaceous earth and the remainder sodium chloride particles.

[0095] Example 18: Different from Example 1, in the method (3) of the morphology control treatment of step S1-3, the carbon nitride sheet is finally heat-treated at a temperature of 100°C for 10 minutes to obtain a carbon nitride substrate.

[0096] Example 19: Different from Example 1, in the method (3) of the morphology control treatment of step S1-3, the carbon nitride sheet is finally heat-treated at a temperature of 110°C for 5 minutes to obtain a carbon nitride substrate.

[0097] Example 20: Different from Example 1, in step S2, the mass ratio of Fe, Ga, Cr and the transmission medium is 2:1:1:0.8.

[0098] Example 21: Different from Example 1, in step S2, the mass ratio of Fe, Ga, Cr and the transmission medium is 5:1:1:1.2.

[0099] Example 22: Different from Example 1, in step S3, the chemical stripping method is: immerse the FeGaCr layered crystals in 800 mL of a mixed solvent of dimethylformamide and acetone in equal mass ratios, and then heat the mixture to 65°C until the interface layer is completely dissolved, thereby achieving the separation of the FeGaCr two-dimensional ferromagnetic material and the carbon nitride substrate.

[0100] Example 23: Different from Example 1, in step S3, the chemical stripping method is: immerse the FeGaCr layered crystals in 1000 mL of a mixed solvent of dimethylformamide and acetone in equal mass ratios, and then heat the mixture to 75°C until the interface layer is completely dissolved, thereby achieving the separation of the FeGaCr two-dimensional ferromagnetic material and the carbon nitride substrate.

[0101] Example 24: Different from Example 1, in step S3, ultrasonic waves are simultaneously applied after heating to perform oscillation treatment, and the parameters of the oscillation treatment are: ultrasonic frequency is 20 kHz, ultrasonic power is 80 W, and ultrasonic time is 30 min.

[0102] Example 25: Different from Example 1, in step S3, ultrasonic waves are simultaneously applied after heating to perform oscillation treatment, and the parameters of the oscillation treatment are: ultrasonic frequency is 23 kHz, ultrasonic power is 90 W, and ultrasonic time is 25 min.

[0103] Example 26: Different from Example 1, in step S3, ultrasonic waves are applied synchronously after heating to perform oscillation treatment, and the parameters of the oscillation treatment are: ultrasonic frequency is 25 kHz, ultrasonic power is 100 W, and ultrasonic time is 20 min.

[0104] Experimental Example: The magnetic strength and Curie temperature of the two-dimensional ferromagnetic materials prepared in Examples 1 to 26 and Comparative Examples 1 to 7 were tested, and the results were as follows:

[0105] 1. Study the effect of carbon nitride flake processing on the performance of two-dimensional ferromagnetic materials

[0106] Comparative Example 1: Different from Example 1, in step S1-2, plasma is not used to treat the carbon nitride sheet.

[0107] Comparative Example 2: Different from Example 1, in the method (1) of morphology control treatment in step S1-3, the PU particles are not subjected to modification treatment.

[0108] Comparative Example 3: Different from Example 1, in the method (1) of the morphology control treatment in step S1-3, the magnetic powder core material is replaced by iron powder.

[0109] Conclusion: Figure 1 , Figure 2 From the variation trend diagrams of the saturation magnetization intensity and (antiferromagnetic transition temperature of the two-dimensional ferromagnetic materials prepared in Examples 1 to 9 and Comparative Examples 1 to 3, it can be concluded that the saturation magnetization intensity and (antiferromagnetic transition temperature of the two-dimensional ferromagnetic material prepared in Comparative Example 1 without using plasma to treat the carbon nitride sheet both show a downward trend. This is because the plasma treatment can effectively clean the surface of the carbon nitride sheet, remove organic matter, inorganic matter and other impurities on the surface, make the surface cleaner, and can activate the surface, increase the chemical activity of the surface, and provide better interface conditions for the subsequent growth of ferromagnetic material films;

[0110] By comparing Example 1, Examples 4 to 5 and Comparative Example 2, it can be seen that in Comparative Example 2, the PU particles are not modified, so that the saturation magnetization and (antiferromagnetic transition temperature are slightly decreased. This shows that although the PU particles can be used as interface modifiers to promote the interaction between nano-silicon oxide, carbon nitride and ferromagnetic materials, improve the interface bonding ability, further improve the bonding effect of the interface layer, and provide the coating with flexibility and adhesion, so that the coating has better performance, the modification to give the PU particles magnetic properties can further promote the performance improvement of the saturation magnetization and (antiferromagnetic transition temperature of the two-dimensional ferromagnetic material.

[0111] By comparing Example 1, Examples 8 to 9 and Comparative Example 3, it can be seen that replacing the magnetic powder core material with iron powder in Comparative Example 3 causes the saturation magnetization and (antiferromagnetic transition temperature to show a downward trend, respectively. Magnetic powder core materials usually have higher magnetic permeability and saturation magnetization, so compared with iron powder, they can more effectively enhance the magnetic properties of PU materials, which helps to improve the responsiveness and efficiency of the material in the electromagnetic field. The magnetic powder core material is a composite soft magnetic material formed by mixing and pressing ferromagnetic powder and insulating medium. The magnetic powder core material is composed of soft magnetic powder particles and insulating medium, wherein the soft magnetic powder particles account for 65% to 85% of the total volume, and the insulating medium accounts for 15% to 35% of the total volume. At the same time, the magnetic powder core material has the characteristics of high magnetic permeability, low coercive force, high Curie temperature, and low loss, which makes it have a better performance improvement effect on the saturation magnetization and (antiferromagnetic transition temperature of two-dimensional ferromagnetic materials.

[0112] 2. Explore the effects of morphology control steps on the properties of two-dimensional ferromagnetic materials

[0113] Comparative Example 4: Different from Example 1, the suspension, pore-forming agent and PEI particles are directly mixed evenly and then sprayed onto the surface of the carbon nitride sheet using a thermal spray gun.

[0114] Comparative Example 5: Different from Example 1, in the method (3) of morphology control treatment in step S1-3, the carbon nitride sheet is not subjected to heat treatment.

[0115] Conclusion: Figure 3 , Figure 4From the variation trend diagrams of the saturation magnetization intensity and (anti) ferromagnetic transition temperature of the two-dimensional ferromagnetic materials prepared in Example 1, Example 10 to Example 19 and Comparative Examples 4 to Comparative Examples 5, it can be concluded that in Comparative Example 4, the suspension, pore-forming agent and PEI particles are directly mixed and uniformly sprayed on the surface of the carbon nitride sheet to form an intermediate layer with gaps. The performance of the two-dimensional ferromagnetic material prepared shows a significant downward trend. This is because the intermediate layer at this time helps to improve the dispersibility of the FeGaCr ferromagnetic material on the carbon nitride sheet, provides more deposition sites for the FeGaCr ferromagnetic material, and can promote the adhesion of the two-dimensional ferromagnetic material on the surface of the carbon nitride sheet through the microporous structure. When the FeGaCr ferromagnetic material is deposited on the carbon nitride sheet in a smaller size, it helps to increase its Curie temperature. However, the presence of micropores will also lead to interface discontinuity between the carbon nitride sheet and the FeGaCr ferromagnetic material. This discontinuity may reduce the magnetic exchange coupling at the interface, thereby affecting the magnetic properties of the FeGaCr ferromagnetic material. Judging from the trend change of Comparative Example 5, after the morphology control treatment is completed, the carbon nitride sheet is not subjected to heat treatment, which can reduce the performance of the two-dimensional ferromagnetic material. This is mainly because heat treatment can assist the interface layer to form chemical bonds with the carbon nitride surface, enhance interface bonding, and further improve the performance of the FeGaCr ferromagnetic material.

[0116] 3. Explore the effect of temperature adjustment in dual temperature zones on the performance of two-dimensional ferromagnetic materials

[0117] Comparative Example 6: Different from Example 1, the temperature gradient is set to between 950 and 1050°C, maintained for 2 days, and then naturally cooled to room temperature, and then the temperature gradient is set to between 1050 and 1000°C and maintained for 4 days.

[0118] Comparative Example 7: Different from Example 1, when |T an -T bn When |≥140, the temperature adjustment is ended and FeGaCr layered crystals are obtained.

[0119] Conclusion: Figure 5 , Figure 6 The saturation magnetization intensity and (anti) ferromagnetic transition temperature of the two-dimensional ferromagnetic materials prepared in Example 1, Example 20-Example 21 and Comparative Examples 6-Comparative Examples 7 show that the performance of the two-dimensional ferromagnetic material prepared by the temperature change of two gradients in Comparative Example 6 is not as good as that of the gradient temperature change of the present application, and in Comparative Example 7, when |T an -T bn|≥140, the performance of the two-dimensional ferromagnetic material prepared by ending the temperature adjustment is slightly worse than that of the gradient temperature change effect of the present application. This is because the gradient change method of the present application can effectively promote the generation of stress in the FeGaCr thin film material during the growth process, thereby guiding the formation of more regular dislocations, which can effectively enhance the stability of the ferromagnetic material. At the same time, this dislocation will not affect the performance of the ferromagnetic material. Based on this, the gradient change method provided by the present application to adjust the growth of the FeGaCr layered film has a decisive influence on the performance of the prepared two-dimensional ferromagnetic material.

[0120] 4. Explore the effect of chemical exfoliation methods on the properties of two-dimensional ferromagnetic materials

[0121] Conclusion: Figure 7 , Figure 8 From the variation trend diagrams of the saturation magnetization intensity and (anti) ferromagnetic transition temperature of the two-dimensional ferromagnetic materials prepared in Examples 1 and 22 to 26, it can be concluded that in Examples 24 to 26, by synchronously applying ultrasonic oscillation treatment to the interface layer after heating, the dissolution effect of the composite solvent on the interface layer is further enhanced, thereby improving the separation effect of the FeGaCr ferromagnetic material.

Claims

1. A two-dimensional ferromagnetic material with a high Curie temperature, characterized in that: The invention is prepared from Fe, Ga, Cr and a transmission medium in a mass ratio of 2-5:1:1:0.8-1.2, wherein the transmission medium is liquid bromine; the Fe is FeCl3·6H2O, the Ga is Ga powder, and the Cr is Cr powder.

2. A method for preparing a two-dimensional ferromagnetic material with a high Curie temperature, for preparing the two-dimensional ferromagnetic material with a high Curie temperature as claimed in claim 1, characterized in that: The following steps are involved: S1. Preparation of carbon nitride substrate S1-1. At a temperature of 22 to 26° C., soak the carbon nitride sheet in 70 to 80% ethanol for 15 to 20 minutes, then rinse the treated carbon nitride sheet with clean water for 4 to 6 times, dry it naturally, and set it aside; S1-2, placing the carbon nitride sheet in a plasma processor, evacuating the vacuum in the plasma processor to 0.02-0.04 mTorr, introducing argon gas, and then subjecting the carbon nitride sheet to plasma treatment at a temperature of 250-300 K; wherein the plasma power is 40-60 W, the plasma treatment time is 40-60 s, the gas flow rate is 60-70 sccm, and the gas pressure is 50-70 mTorr; S1-3, performing morphology control treatment on the surface of the carbon nitride sheet after the plasma treatment so that the surface has gaps, thereby obtaining a carbon nitride substrate; S2. Preparation of layered crystals Fe, Ga, and Cr are sealed in a sealed quartz tube as precursors. The transmission medium is prepared and introduced into the quartz tube. Then, the tube is placed in a dual-temperature zone tube furnace and vacuumed to ≤10 -4 Pa, and then adjust the temperature of the double temperature zone, where the temperature of one end after adjustment n times is recorded as T an The temperature at the other end is T bn , and a thin film is grown on the carbon nitride substrate prepared in step S1, and the film growth thickness is D n , when |T an -T bn When |≥150, the temperature adjustment is terminated and FeGaCr layered crystals are obtained; Among them, T an , T bn Temperature change, D n The thickness change satisfies the following formula: T an =T b(n-1) +25n×(-1) n+1 (1) T bn =T a(n-1) -50n×(-1) n-1 (2) k is the coefficient, 0.3≤k≤0.5, T b0 is the initial temperature of one end, in °C, satisfying 900≤T b0 ≤1000; T a0 is the initial temperature of the other end, in °C, satisfying 850≤T a0 ≤950;D n is the film deposition thickness, in nm; n is the number of adjustments; t n is the interval between the nth temperature adjustment and the last temperature adjustment, in days, satisfying 2≤t n ≤4; S3, post-processing By chemically exfoliating the FeGaCr layered crystals and then removing the carbon nitride substrate, a two-dimensional ferromagnetic material with a high Curie temperature is obtained.

3. The method for preparing a two-dimensional ferromagnetic material with a high Curie temperature according to claim 2, characterized in that: In step S1-3, the method of morphology control processing is: (1) Adding nano-silicon oxide particles, modified PU particles and a composite solvent to a mixing bottle in a mass ratio of 22 to 26:5 to 7:12 to 14, sealing the mixing bottle, and placing the mixing bottle in an oil bath at 55 to 58° C. and stirring for 10 to 11 hours to form a suspension; wherein the composite solvent in the mixing bottle is a mixture of N,N-dimethyl sulfoxide and N-methylpyrrolidone in a weight ratio of 1 to 1.5:1; (2) taking 2 / 3 of the suspension and mixing them according to the weight ratio of suspension: pore-forming agent of 8-10:0.6-0.8, stirring until molten, and then using a hot spray gun to evenly spray it on the surface of the carbon nitride sheet, standing for 15-20 minutes to form an interface layer with pores, and then continuing to raise the temperature of the oil bath to 85-88°C, and adding PEI particles accounting for 5-12wt.% of the mass fraction of the remaining suspension to the mixing bottle, stirring and dispersing for 5-7h to form a mixed solution, and again using a hot spray gun to evenly spray the mixed solution on the surface of the interface layer, standing for 15-20 minutes to obtain a buffer layer; wherein the thickness of the interface layer is 2-3μm, and the thickness of the buffer layer is 0.5-1μm; (3) Finally, the carbon nitride sheet is heat treated at a temperature of 100 to 110° C. for 5 to 10 minutes to obtain a carbon nitride substrate.

4. The method for preparing a two-dimensional ferromagnetic material with a high Curie temperature according to claim 3, characterized in that: In step (1), the preparation method of the modified PU particles is: at room temperature, the magnetic powder core material, the solvent and the dispersant are stirred and mixed at a mass ratio of 8-12:4-6:2-3 at a rate of 100-300r / min to obtain a magnetic suspension, and then the temperature is adjusted to 80-100°C, the magnetic suspension and the PU particles are mixed in a ratio of 10-15mL:4-8g, and finally the temperature is raised to 120-140°C for curing treatment for 1-2h, washed with water and dried to obtain modified PU particles.

5. The method for preparing a two-dimensional ferromagnetic material with a high Curie temperature according to claim 4, characterized in that: The solvent is dimethylformamide, n-butanol or n-hexane.

6. The method for preparing a two-dimensional ferromagnetic material with a high Curie temperature according to claim 4, characterized in that: The dispersant is polyacrylic acid or sodium lauryl sulfate.

7. The method for preparing a two-dimensional ferromagnetic material with a high Curie temperature according to claim 3, characterized in that: In step (2), the pore-forming agent comprises, by weight percentage, 25-30% polystyrene, 15-20% carbon black, 5-8% diatomaceous earth and the remainder sodium chloride particles.

8. The method for preparing a two-dimensional ferromagnetic material with a high Curie temperature as claimed in claim 2, characterized in that: In step S3, the chemical stripping method is: immerse the FeGaCr layered crystals in 800-1000 mL of a mixed solvent of dimethylformamide and acetone in equal mass ratios, and then heat the mixture to 65-75° C. until the interface layer is completely dissolved, thereby achieving separation of the FeGaCr two-dimensional ferromagnetic material and the carbon nitride substrate.

9. The method for preparing a two-dimensional ferromagnetic material with a high Curie temperature according to claim 8, characterized in that: After heating, ultrasonic waves are simultaneously applied to perform oscillation treatment, wherein the parameters of the oscillation treatment are: ultrasonic frequency of 20 to 25 kHz, ultrasonic power of 80 to 100 W, and ultrasonic time of 20 to 30 min.